Abordaje logoterapéutico para la prevención de recaídas en el consumo de drogas, en los residentes de la Comunidad Terapéutica Aprender a Vivir, en el periodo de marzo a julio del 2017 - Bossano Muñoz, Ronny Martín (2018)
The following work represents the systematization of a model of logotherapeutic intervention applied in the “Comunidad Terapeutica Aprender A Vivir”, in the period from March to July 2017. The need to carry out this project arises with the intention of complementing the work done in this institution. from a new humanistic focus, promoting a person-centered vision and this way enabling an alternative strategy for the prevention of relapses in drug use. The model that allows to implement a logotherapeutic approach that is constituted in five phases: introduction to logistics, recognition of risk factors that lead to a relapse, application of logotherapeutic techniques and preparation of a logotherapeutic life project. So within this report you can know the results obtained from the intervention carried out in the institution. Describing the systemic way for the application of a logotherapeutic model and its effectiveness for the treatment of addictions, focusing mainly on the prevention of relapses in drug abuse. Finally, conclusions and recommendations of the achievements obtained with the application of this project are proposed; In such way, the impact that this intervention model had on the people with whom we worked within the institution, the same with which the search was conducted for a meaning for their own existence, from a logotherapeutic aspect.